Chalcone Based Colorimetric Sensor for Anions: Experimental and TD-DFT Study - Adita Silvia Fitriana; Harno Dwi Pranowo; Bambang Purwono (Universitas Gadjah Mada, 2016)
The interactions between sensor chalcone of 3-(4-hydroxy-3-methoxyphenyl)-1-phenyl-2-propen-1-one (1) and anions (F–, Cl–, Br–, CN–, CO32–, and SO42–) have been experimentally and TD-DFT theoretically investigated. Sensor (1) showed a naked-eye detectable color change from yellow to red upon addition of F–, CO32–, CN–, and SO42– anions in DMSO, whereas no significant color change was observed upon addition of Cl– and Br– anions. The interaction models were predicted by optimizing (1)-anion complex using DFT/B3LYP method. Optimized (1)-anion complexes showed that sensor (1) was deprotonated by CO32–, CN–, F–, and SO42–. The formation of deprotonated sensor (1)– was responsible for the colorimetric signaling. Absorption spectra of neutral and deprotonated sensor were calculated using TD-DFT method. The calculated spectra were in good agreement with experimental results.